FGF21 and Cardiac Physiopathology - Planavila, Anna; Redondo-Angulo, Ibon; Villarroya, Francesc (Frontiers in Endocrinology, 2015)
The heart is not traditionally considered either a target or a site of fibroblast growth factor-21 (FGF21) production. However, recent findings indicate that FGF21 can act as a cardiomyokine; that is, it is produced by cardiac cells at significant levels and acts in an autocrine manner on the heart itself. The heart is sensitive to the effects of FGF21, both systemic and locally generated, owing to the expression in cardiomyocytes of β-Klotho, the key co-receptor known to confer specific responsiveness to FGF21 action. FGF21 has been demonstrated to protect against cardiac hypertrophy, cardiac inflammation, and oxidative stress. FGF21 expression in the heart is induced in response to cardiac insults, such as experimental cardiac hypertrophy and myocardial infarction in rodents, as well as in failing human hearts. Intracellular mechanisms involving PPARα and Sirt1 mediate transcriptional regulation of the FGF21 gene in response to exogenous stimuli. In humans, circulating FGF21 levels are elevated in coronary heart disease and atherosclerosis, and are associated with a higher risk of cardiovascular events in patients with type 2 diabetes. These findings provide new insights into the role of FGF21 in the heart and may offer potential therapeutic strategies for cardiac disease.